ANALISA DAN RANCANGAN SISTEM INFORMASI MANAJEMEN ADMINISTRASI PEMBERDAYAAN KESEJAHTERAAN KELUARGA KOTA SIBOLGA - Imran Lubis; Divi Handoko (STMIK KAPUTAMA, 2019)
Family welfare empowerment (PKK) is a community organization with 10 main programs that empower women to participate in Indonesia's development. The administrative process that has not been properly systemmed causes less optimal and efficient provision of data and information. In this study, the technique of developing the PKK Management Information System applies the Rapid Application Development (RAD) method, where this method has the advantage of being short and fast. The results of the SIM PKK design can provide convenience in providing accurate, fast data for policy making and also able to improve performance and efficiency in KDP organizations.